Genetic markers on the distribution of ancient marine hunters in Priokhotye - B. A. Malyarchuk (Вавиловский журнал генетики и селекции, 2020)
This is a review of studies on the genetic polymorphism of modern and ancient populations of the north of Asia and America, with the aim of reconstructing the history of migrations of ancient marine hunters in the Okhotsk Sea region. The data on mitochondrial DNA polymorphism and the “Arctic” mutation distribution – the rs80356779-A variant of the CPT1A gene – were analyzed. It is known that the “Arctic” variant of the CPT1A gene is widely distributed in modern populations of the Eskimos, Chukchis, Koryaks, and other peoples of the Okhotsk Sea region, whose economic structure is associated with marine hunting. According to paleogenomic data, the earliest cases of the “Arctic” variant of the CPT1A gene were found in the Greenland and Canadian Paleoeskimos (4 thousand years ago), among representatives of the Tokarev culture of the Northern Priokhotye (3 thousand years ago), and among the bearers of the culture of the late Jomon of Hokkaido (3.5–3.8 thousand years ago). The results of the analysis revealed several migration events associated with the spread of marine hunters in the Okhotsk Sea region. The latest migration, which left traces on bearers of the Epi-Jomon culture (2.0–2.5 thousand years ago), introduced the mitochondrial haplogroup G1b and the “Arctic” variant of the CPT1A gene from the north of Priokhotye to Hokkaido and neighboring territories of the Amur Region. Traces of earlier migration, which also brought the “Arctic” mutation, were recorded in the Hokkaido population of the late Jomon period (3.5–3.8 thousand years ago). A phylogenetic analysis of mitochondrial genomes belonging to the rare haplogroup C1a, found in populations of the Far East and Japan, but phylogenetically related to the C1-haplogroups of the Amerindians, was carried out. The results of the analysis showed that the divergence of mitochondrial lineages within the C1a haplogroup occurred in the range from 7.9 to 6.6 thousand years ago, and the age of the Japanese branch of the C1a haplogroup is approximately 5.2 thousand years. It is not yet known whether this migration is associated with the spread of the “Arctic” variant of the CPT1A gene or the presence of C1a haplotypes in the population of the Japanese islands marks another, earlier, episode of the migration history linking the populations of Northwest Pacific and North America.